Divergent Regulation of CBF Regulon on Cold Tolerance and Plant Phenotype in Cassava Overexpressing Arabidopsis CBF3 Gene - An, Dong; Ma, Qiuxiang; Yan, Wei; Zhou, Wenzhi; Liu, Guanghua; Zhang, Peng (Frontiers in Plant Science, 2016)
Cassava is a tropical origin plant that is sensitive to chilling stress. In order to understand the CBF cold response pathway, a well-recognized regulatory mechanism in temperate plants, in cassava, overexpression of an Arabidopsis CBF3 gene is studied. This gene renders cassava increasingly tolerant to cold and drought stresses but is associated with retarded plant growth, leaf curling, reduced storage root yield, and reduced anthocyanin accumulation in a transcript abundance-dependent manner. Physiological analysis revealed that the transgenic cassava increased proline accumulation, reduced malondialdehyde production, and electrolyte leakage under cold stress. These transgenic lines also showed high relative water content when faced with drought. The expression of partial CBF-targeted genes in response to cold displayed temporal and spatial variations in the wild-type and transgenic plants: highly inducible in leaves and less altered in apical buds. In addition, anthocyanin accumulation was inhibited by downregulating the expression of genes involved in its biosynthesis and by interplaying between the CBF3 and the endogenous transcription factors. Thus, the heterologous CBF3 modulates the expression of stress-related genes and carries out a series of physiological adjustments under stressful conditions, showing a varied regulation pattern of CBF regulon from that of cassava CBFs.